Outcome of Lobectomy in Inflammatory Lung Diseases: A Four-Year Experience at Nishtar Hospital Multan - Muhammad Kaleem Ullah, Muhammad Sami Ullah, Maria Angbeen Hashmi, Mansoor Ali, Muhammad Raza, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Inflammatory lung diseases such as bronchiectasis, pulmonary destruction related to tuberculosis, chronic abscess, and fungal cavities are still common indications of lung resection in developing countries. Lobectomy is important when medical therapy is unsuccessful, although there is still little outcome data from local centres. Objective: To assess postoperative results of lobectomy done for inflammatory lung diseases over 4 years at Nishtar Hospital Multan. Methodology: A retrospective study was done in the Department of Thoracic Surgery, Nishtar Hospital Multan from January 2020 to December 2022. All patients who had undergone lobectomy for non-malignant inflammatory lung disease were included. Demographic data, cause of disease, type of lobectomy, operative time, complications, hospitalization, and recovery after the operation were evaluated. Results: A total of 126 patients were patients who underwent lobectomy for inflammatory lung diseases. The most common indication was bronchiectasis (48%), followed by post-tuberculous destroyed lung 34%, chronic lung abscess 10% and fungal cavity 8%. The average operative time was 138+-22 minutes, and the average hospital stay was 7.6+3.1 days. Postoperative complications occurred in 28% of patients: prolonged air leak (12%), empyema (6%), wound infection (5%) and atelectasis requiring bronchoscopy (5%). Mortality was 1.6% (n=2). Symptomatic improvement was obtained in 92% of the cases at 3-month follow-up. Conclusion: Lobectomy is a safe and effective way of treating selected inflammatory lung diseases with acceptably low morbidity and low mortality. Early referral and careful selection of patients can have a major impact on improving outcomes. Keywords: Lobectomy, Inflammatory lung disease, Bronchiectasis, Tuberculosis, Thoracic surgery.